Analisis Indeks Efisiensi Logistik (Iel) Pada Saluran Pemasaran Buah Naga (Hylocereus Spp) Di Kabupaten Bulukumba - Halim, Hasriliandi; Zailan, Ahmad; Gunawan, Rifaldi (CV. SINAR HOWUHOWU, 2025)
Marketing channels are one of the key factors determining the success of marketing perishable horticultural commodities, such as dragon fruit (Hylocereus spp.). Bulukumba Regency is one of the major dragon fruit production areas in South Sulawesi Province with considerable production potential; however, it has not been supported by an efficient marketing and logistics system. This study aims to analyze the level of logistics efficiency across dragon fruit marketing channels in Bulukumba Regency using the Logistics Efficiency Index (EIL). The research employed a quantitative descriptive approach with a survey method involving farmers, collectors, market traders, and wholesalers. Data analysis included mapping marketing channels, calculating logistics costs, product value, and determining the Logistics Efficiency Index (IEL) for each marketing channel. The results indicate that there are four main dragon fruit marketing channels in Bulukumba Regency with varying levels of efficiency. Marketing Channel I is the most efficient channel with the lowest EIL value of 0.16, while Marketing Channels II and III have EIL values of 0.27 and 0.32, respectively, and are classified as less efficient. Marketing Channel IV is the least efficient channel with an EIL value of 0.39. High transportation costs, storage costs, sorting and post-harvest handling costs, as well as product losses are the main factors contributing to low logistics efficiency. Therefore, the development of dragon fruit marketing in Bulukumba Regency should focus on shortening the supply chain and improving the logistics system to minimize logistics costs and enhance marketing efficiency.